Word equity markets: a new approach for segmentation - Curto, J. D. (2018)
This paper is an assessment of international equity-market integration and uses an innovative approach to segment equity markets into related geographic areas. Our focus is on the relationships among the returns of the dominant national equity indexes by continent. To understand how these indexes have evolved, we will concentrate on a reduced number of dimensions extracted from principal components analysis. We will demonstrate that each one of these components is particularly associated with certain groups of nations and less associated with others.